Theater careers : a realistic guide - Donahue, Tim, 1952- (University of South Carolina Press, 2012)
Theater Careers is designed to empower aspiring theater professionals to make savvy, informed decisions through a concise overview of how to prepare for and find work in the theater business. Tim Donahue and Jim Patterson offer well-researched information on various professions, salary ranges, educational and experience requirements, and other facets certain to enlighten students contemplating a theater career, as well as inform counselors, teachers, and parents of available opportunities and the demands of each path. --from publisher description.